1995
DOI: 10.1016/0370-2693(95)00124-4
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields in a thermal background

Abstract: The one-loop effective action for a slowly varying electromagnetic field is computed at finite temperature and density using a real-time formalism.We discuss the gauge invariance of the result. Corrections to the Debye mass from an electric field are computed at high temperature and high density. The effective coupling constant, defined from a purely electric weak-field expansion, behaves at high temperature very differently from the case of a magnetic field, and does not satisfy the renormalization group equa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 20 publications
5
83
2
Order By: Relevance
“…5, we calculate the thermal contribution to Schwinger's famous pair-production formula [16] for constant electric background fields in the low-temperature limit. Here, a thermal one-loop contribution surprisingly does not exist [7,9], since the thermal one-loop effective action is purely real by construction. Hence, the findings of Sec.…”
Section: Introductionmentioning
confidence: 91%
“…5, we calculate the thermal contribution to Schwinger's famous pair-production formula [16] for constant electric background fields in the low-temperature limit. Here, a thermal one-loop contribution surprisingly does not exist [7,9], since the thermal one-loop effective action is purely real by construction. Hence, the findings of Sec.…”
Section: Introductionmentioning
confidence: 91%
“…͑11͒ is allowed if the frequency is also much smaller than k B T with k B the Boltzmann constant and N 1/3 . 42 Also, in the presence of particle backgrounds the Euler-Heisenberg effective Lagrangian density ͑11͒ has to be corrected by adding the so-called effective Lagrangian density at finite temperature and chemical potential. 8,43,44 It turns out that the finite-temperature twoloop contribution to the effective Lagrangian density is dominant with respect to the one-loop contribution at temperatures such that k B T Ӷ m e .…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Thermal effects generalize the classical results of Schwinger in the weak field limit (Heisenberg and Euler, 1936;Schwinger, 1951;Weisskopf, 1936). It was pioneered by Dittrich (1979) who investigated the thermal effects in combination with an external magnetic field, and later a comprehensive study using the real time formalism in the case of an general electromagnetic field background was performed by Elmfors and Skagerstam (1995) (see also Gies (1999a)). The dispersion relation, including dispersive effects, was discussed by Gies (1999b), and it was later shown that in a ther-1 Casimir considered particle-particle and particle-plate (Casimir and Polder, 1948), and plate-plate systems (Casimir, 1948), since the problem stemmed from research on colloidal solutions, but is most clearly represented by the parallel plate example.…”
Section: Effective Field Theory Of Photon-photon Scatteringmentioning
confidence: 99%